ECTHR_CHAMBER 63539/19 vom 20. Dezember 2022 , AFFAIRE ZEMMOUR c. FRANCE - Ecthr Chamber (2022)
Non-violation de l'article 10 - Liberté d'expression-{général} (Article 10-1 - Liberté d'expression); No violation: 10;10-1